Functional Reliability Assessment of Water Transmission Buildings of Urban Water Supply Systems - Tkachuk, Alexander; Novytska, Olha; Shevchuk, Anton; Azizova, Anna (International Journal of Engineering and Technology, 2018)
Continuous operation of water supply systems of settlements, industrial and agricultural objects is one of the topical problems in Ukraine. The most costly, complicated and responsible for reliable water supply in modern water supply systems are the complexes of water transmission buildings, which include pump stations, water mains, pressure and regulation facilities. They are located on a large territory, hydraulically connected with each other and require an integrated assessment of reliability based on their constructive and functional indicators, as well as the normative consolidation of methods and indicators of reliability assessment. It is proposed to assess the functional reliability by constant coefficients of operational availability. They should be complied with the normative values of the operating efficiency factors. The numerical values of the operating efficiency factors for each of three categories of water supply systems in conditions of water supply reduction and limitation are determined on the basis of the present standards. The basic principles of the methodology of engineering calculations of functional reliability of water transmission buildingsâ€™ complexes (WTBC) are theoretically substantiated. The expediency and reliability of the assessment of functional reliability is confirmed by calculations. Improvement of functional reliability of WTBC can be provided by rational design schemes and efficient operation with intensive rehabilitation.Â Â